Use of Erythropoietin in patients with multiple myeloma - Egerer, Gerlinde; Harter, Christoph; Karthaus, Meinolf; Ho, Anthony Dick; Goldschmidt, Hartmut (Onkologie, 2003)
The prevalence of tumour anaemia in patients with multiple myeloma is greater than 80%. At the time of diagnosis 20% of these patients are already anaemic. In about 70% of patients with multiple myeloma, recombinant human erythropoietin (r-HuEPO) leads to a reduction in transfusion frequency, resulting in a drop in transfusion- related side-effects like infections and immune reactions, iron overload and hyperviscosity which often negatively influence the course of disease. A further reason for the use of erythropoietin is to achieve and maintain high haemoglobin levels (11-12 g/dl), which are of considerable prognostic significance in patients with multiple myeloma. Increasing Hb levels with r-HuEPO also improve the quality of life of patients, thus leading to better therapy compliance. The trade-off between high costs of an erythropoietin treatment and lower indirect costs (infusion material, personal equipment, patient transport costs, etc.) should be evaluated. Nevertheless, an exact definition of patients for whom the use of erythropoietin is beneficial is warranted. The pathogenesis of anaemia and the clinical experiences of erythropoietin in patients with multiple myeloma are discussed.
Gesehen am 10.12.2021